Lithium titanate negative electrode material as well as preparation method and application thereof

The lithium titanate negative electrode material was prepared by spray drying, and the synergistic effect of lanthanum source and polyvinyl alcohol was used to solve the shortcomings of graphite negative electrode material in lithium-ion batteries, significantly improving the performance of the battery.

CN119390113APending Publication Date: 2025-02-07HEBEI GELLEC NEW ENERGY MATERIAL SCI&TECHNOLOY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411477211.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Graphite, the negative electrode material of existing lithium-ion batteries, has problems with low lithium-ion diffusion coefficient, poor cycle life and safety performance.

Method used

The lithium titanate negative electrode material is prepared by spray drying. The ionic conductivity and structural stability of the material are improved through the synergistic effect of lanthanum source and polyvinyl alcohol.

Benefits of technology

The ionic conductivity, cyclic stability and rate performance of lithium titanate negative electrode materials have been significantly improved, and the thermal stability and chemical stability of the battery have been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390113A_ABST
    Figure CN119390113A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium titanate negative electrode material and a preparation method and application thereof, and the preparation method of the lithium titanate negative electrode material comprises the following steps: uniformly mixing a titanium source, a lithium source, a lanthanum source, polyvinyl alcohol and a solvent, carrying out spray drying to obtain precursor powder, calcining the precursor powder at 700-900 DEG C for 5-10 hours, and cooling to room temperature to obtain the lithium titanate negative electrode material. According to the invention, the ionic conductivity of the lithium titanate negative electrode material is synergistically enhanced through polyvinyl alcohol and lanthanum oxide, the introduction of polyvinyl alcohol can play a better dispersion role, and the formation of a more uniform and better-quality lithium titanate negative electrode material is facilitated by improving the rheological property of the material in the spray drying process; the lanthanum oxide is introduced into the lithium titanate material, so that the crystal structure and the electronic structure of the lithium titanate can be changed, the overall performance of the lithium titanate material can be improved, and the electrochemical performance of the lithium titanate material can be optimized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a lithium titanate negative electrode material and a preparation method and application thereof. Background Art

[0002] Energy storage and energy conversion have become basic needs of people and key issues related to our daily lives. As people pay more and more attention to the consumption of fossil fuels, renewable and cleaner energy and energy storage equipment have also attracted much attention. For example: solar energy, wind energy, tidal energy. Due to the variability of energy sources such as wind energy and solar energy, energy storage is particularly important in the effective use of new energy. At the same time, due to record high oil prices and serious global warming problems, energy-saving and environmentally friendly technologies in automotive product development are more prominent as major challenges facing the global automotive industry today.

[0003] Electrochemical energy storage devices have become an indispensable part of people's lives. Lithium-ion battery technology has been the key to the development of portable electronic products in the past. Now it has officially begun to enter the field of electric vehicles. Since the 1990s, the commercialization of lithium-ion batteries has greatly promoted the development of modern electronic technology. Among all commercial battery technologies, the advantages of lithium-ion batteries are their high energy density, long cycle life and wide operating temperature range.

[0004] Currently, graphite is mainly used as the negative electrode material for lithium-ion batteries on the market. However, there are several problems with graphite as the negative electrode material for lithium-ion batteries: the lithium ion diffusion coefficient is low, resulting in poor rate performance of lithium-ion battery products; the graphite negative electrode expands in volume during the process of lithium insertion and extraction, resulting in poor cycle life; the graphite negative electrode is prone to produce lithium dendrites, resulting in safety problems. Summary of the invention

[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a lithium titanate negative electrode material. The preparation method adopts a spray drying method and uses a lanthanum source and polyvinyl alcohol to collaboratively prepare the lithium titanate negative electrode material.

[0006] Another object of the present invention is to provide a method for preparing a lithium titanate negative electrode sheet.

[0007] Another object of the present invention is to provide application of the above-mentioned lithium titanate negative electrode material in a battery.

[0008] The purpose of the present invention is achieved through the following technical solutions.

[0009] A preparation method of a lithium titanate negative electrode material comprises: mixing a titanium source, a lithium source, a lanthanum source, polyvinyl alcohol and a solvent until uniform to obtain a B solution (white solution), spray drying the B solution to obtain a precursor powder, calcining the precursor powder at 700 to 900° C. for 5 to 10 hours, and cooling to room temperature to obtain a lithium titanate negative electrode material.

[0010] In the above technical solution, the preparation method of lithium titanate negative electrode material comprises the following steps:

[0011] Step 1, mixing a titanium source, a lithium source and a solvent until uniform, to obtain a solution A, wherein the ratio of lithium in the lithium source to titanium in the titanium source is (4.1-4.7):(4.7-5.4) in terms of molar fractions;

[0012] In step 1, the lithium source is one or a mixture of lithium hydroxide, lithium carbonate and lithium acetate, and the titanium source is one or a mixture of titanium dioxide, tetrabutyl titanate and titanium isopropoxide.

[0013] In step 1, the ratio of the amount of lithium in the lithium source to the mass of the solvent is (200-300): (150-200), the unit of the amount of lithium is mmol, and the unit of the mass is g.

[0014] In step 1, the solvent is one or a mixture of water, ethanol and isopropanol.

[0015] Step 2, mixing the A solution, the lanthanum source and the polyvinyl alcohol until uniform, obtaining a B solution, spray drying, and obtaining a precursor powder, wherein the ratio of the amount of lithium in the lithium source, the amount of lanthanum in the lanthanum source and the mass fraction of polyvinyl alcohol is (0.1-1): (0.001-0.05): (0.1-3), the unit of the mass fraction is g, and the unit of the amount of substance is mmol;

[0016] In step 2, the lanthanum source is one or a mixture of lanthanum oxide, lanthanum carbonate and lanthanum nitrate.

[0017] In step 2, solution A, lanthanum source and polyvinyl alcohol are mixed and stirred until uniform.

[0018] In step 2, the inlet temperature of the spray drying is 180-210° C., the pressure of the spray drying is 0.1-0.5 MPa, and the feed rate of the spray drying is 100-500 mL / h.

[0019] In step 2, the ratio of the amount of lithium in the lithium source, the amount of lanthanum in the lanthanum source and the mass fraction of polyvinyl alcohol is preferably (0.1-1): (0.01-0.02): (0.25-0.6), the unit of the mass fraction is g, and the unit of the amount of substance is mmol.

[0020] Step 3, calcining the precursor powder at 700-900° C. for 5-10 hours, and cooling to room temperature to obtain a lithium titanate negative electrode material.

[0021] Use of polyvinyl alcohol and lanthanum source in improving the ionic conductivity of lithium titanate.

[0022] A lithium titanate negative electrode plate comprises: a current collector and a negative electrode material loaded on the current collector, wherein the negative electrode material is the lithium titanate negative electrode material.

[0023] A method for preparing a lithium titanate negative electrode sheet comprises: uniformly mixing the lithium titanate negative electrode material, acetylene black, a binder and N-methylpyrrolidone (NMP) to obtain an electrode slurry (the electrode slurry is a smooth and uniform viscous substance), applying the electrode slurry to the surface of a current collector, and drying to obtain a lithium titanate negative electrode sheet, wherein the ratio of the lithium titanate negative electrode material, acetylene black and the binder is (7-8.5):(0.5-2.0):(0.5-2.5) by mass.

[0024] In the above technical solution, the lithium titanate negative electrode material, acetylene black and a binder are firstly mixed evenly, and then N-methylpyrrolidone (NMP) is added and mixed evenly to obtain the electrode slurry.

[0025] In the above technical solution, the ratio of the volume fraction of N-methylpyrrolidone (NMP) to the mass fraction of lithium titanate negative electrode material is (6-12): (0.8-1.5), the unit of volume fraction is mL, and the unit of mass fraction is g.

[0026] In the above technical solution, the binder is polyvinylidene fluoride (PVDF).

[0027] In the above technical solution, the lithium titanate negative electrode material, acetylene black and binder are mixed uniformly by grinding, and the grinding time is 5 to 10 minutes.

[0028] In the above technical solution, the drying temperature is 50-90° C. and the drying time is 0.1-2 hours.

[0029] The above-mentioned lithium titanate negative electrode material is used to improve the capacity retention rate in batteries.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] The present invention synergistically enhances the ionic conductivity of lithium titanate negative electrode materials through polyvinyl alcohol and lanthanum oxide, wherein the introduction of polyvinyl alcohol can play a better dispersing role when the titanium source, lithium source and lanthanum source are mixed, and helps to form a more uniform and better quality lithium titanate negative electrode material by improving the rheological properties of the material during the spray drying process; by adjusting the amount of polyvinyl alcohol added, the shape of the lithium titanate negative electrode material can be significantly affected, and a more regular spherical lithium titanate negative electrode material can be prepared; the introduction of lanthanum oxide into the lithium titanate material can change the crystal structure and electronic structure of the lithium titanate, which helps to improve the overall performance of the lithium titanate material, so that it has better thermal stability and chemical stability (cycle stability and rate performance). BRIEF DESCRIPTION OF THE DRAWINGS

[0032] FIG1(A) is a SEM of the lithium titanate negative electrode material prepared in Comparative Example 1 at 1.00KX;

[0033] FIG1(B) is a SEM of the lithium titanate negative electrode material prepared in Comparative Example 1 at 5.00KX;

[0034] FIG1(C) is a SEM of the lithium titanate negative electrode material prepared in Example 2 at 1.00KX;

[0035] FIG1(D) is a SEM of the lithium titanate negative electrode material prepared in Example 2 at 5.00KX;

[0036] Figure 2 XRD of the lithium titanate negative electrode material prepared in Example 2;

[0037] Figure 3 XRD of the lithium titanate negative electrode material prepared in Comparative Example 1;

[0038] Figure 4 The lithium ion battery prepared in Example 7 was subjected to a rate test of 200 cycles at a current density of 0.5C;

[0039] Figure 5 The lithium ion battery prepared in Comparative Example 5 was subjected to a rate test of 200 cycles at a current density of 0.5C;

[0040] Figure 6 for Figure 4 Voltage, capacity, current and energy from cycle 75 to 95. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0042] The raw materials involved in the following embodiments are as follows:

[0043] Titanium dioxide, 99% pure;

[0044] Lithium carbonate, purity 99.5%;

[0045] Lanthanum oxide, purity 99.99%;

[0046] Polyvinyl alcohol, molecular weight (Mw) ~205,000;

[0047] Ion conductivity test: The powder was placed in a tabletting mold and pressed into a disc with a thickness of 2 mm and a diameter of 10 mm. The ion conductivity was obtained by using a four-probe method at room temperature and a relative humidity of 100%. The powder was one of the lithium titanate negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3.

[0048] Capacity retention rate: The lithium-ion battery was installed on a battery testing system (Shenzhen Xinwei Electronics Co., Ltd. CT-3008), the test temperature was a constant 25°C, the voltage window was 1.0~3V, the lithium-ion battery was charged and discharged, the capacity attenuation of the lithium-ion battery was recorded, and the battery capacity retention rate was obtained.

[0049] In the following examples, water is deionized water.

[0050] Embodiments 1 to 5

[0051] A method for preparing a lithium titanate negative electrode material comprises the following steps:

[0052] Step 1, mixing a titanium source, a lithium source and a solvent (water) until uniform, to obtain a solution A, wherein, in terms of the amount of substance, the ratio of lithium in the lithium source to titanium in the titanium source is 4.50:5.01, the ratio of the amount of substance of lithium in the lithium source to the mass fraction of the solvent is 250:200, the unit of the amount of substance is mmol, the unit of the mass fraction is g, the lithium source is lithium carbonate, and the titanium source is titanium dioxide;

[0053] Step 2, mixing solution A, lanthanum source and polyvinyl alcohol, stirring magnetically at 350r / min for 0.5h until uniform, obtaining solution B (white solution), spray drying solution B to obtain a precursor powder, wherein the ratio of the amount of lithium in solution A, the amount of lanthanum in the lanthanum source and the mass fraction of polyvinyl alcohol is X (X value is shown in Table 1), the unit of mass fraction is g, the unit of amount of substance is mmol, the inlet temperature of spray drying is 200°C, the pressure is 0.3MPa, the feed rate is 200mL / h, and the lanthanum source is lanthanum oxide;

[0054] Step 3, placing the precursor powder in a muffle furnace, calcining at 800° C. for 8 h, cooling to room temperature, and grinding to obtain a lithium titanate negative electrode material.

[0055] Table 1

[0056] Example X Example 1 0.3:0.0057:0.22 Example 2 0.3:0.0114:0.44 Example 3 0.3:0.0171:0.66 Example 4 0.3:0.0057:0.44 Example 5 0.3:0.0114:0.22

[0057] Comparative Example 1

[0058] A method for preparing a lithium titanate negative electrode material comprises: placing solution A in Example 1 in a forced air drying oven, drying at 60° C. for 16 hours to obtain a first substance, placing the first substance in a muffle furnace, calcining at 800° C. for 8 hours, cooling to room temperature, and grinding to obtain a lithium titanate negative electrode material (pure LTO powder).

[0059] Comparative Example 2

[0060] A method for preparing a lithium titanate negative electrode material is basically the same as that of Example 2, except that polyvinyl alcohol is not added in Comparative Example 2.

[0061] Comparative Example 3

[0062] A method for preparing a lithium titanate negative electrode material is substantially the same as that of Example 2, except that no lanthanum source (lanthanum oxide) is added in Comparative Example 3.

[0063] Examples 6 to 10 and Comparative Examples 4 to 6

[0064] A lithium ion battery comprises: a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is a pure lithium sheet, the separator is a PP-based film, the electrolyte is a mixture of an electrolyte and a solvent, the electrolyte in the electrolyte is lithium hexafluorophosphate (LiPF6), the solvent in the electrolyte is ethyl carbonate, methyl carbonate and dimethyl carbonate, the ratio of ethyl carbonate, methyl carbonate and dimethyl carbonate is 1:1:1 by volume, the concentration of the electrolyte in the electrolyte is 1.0M, the positive electrode, the negative electrode, the separator and the electrolyte are assembled into 20 25-type lithium-ion battery, the protective gas of the glove box is Ar gas, and the method for preparing the negative electrode includes: mixing the lithium titanate negative electrode material, acetylene black and the binder, grinding for 8 minutes until uniform, then adding N-methylpyrrolidone (NMP), stirring until uniform, to obtain an electrode slurry (the electrode slurry is a smooth and uniform viscous substance), applying the electrode slurry to the back of a clean and flat copper foil (current collector) with an applicator, and drying it in an oven at 80°C for 0.5h to obtain a negative electrode (the loading amount of the negative electrode slurry is 25±3mg / cm 2 , the thickness of the coating formed by the negative electrode slurry after drying is 0.8±0.05um), wherein the ratio of the volume fraction of N-methylpyrrolidone (NMP) to the mass fraction of the lithium titanate negative electrode material is 10:1.25, the unit of volume fraction is mL, the unit of mass fraction is g, and the ratio of the lithium titanate negative electrode material, acetylene black and the binder is 8:1:1 by mass, the binder is polyvinylidene fluoride (PVDF), and the lithium titanate negative electrode material is one of the lithium titanate negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3.

[0065] Table 2

[0066] Lithium-ion battery Preparation of lithium titanate negative electrode material for lithium-ion batteries Example 6 Example 1 Example 7 Example 2 Example 8 Example 3 Example 9 Example 4 Example 10 Example 5 Comparative Example 4 Comparative Example 1 Comparative Example 5 Comparative Example 2 Comparative Example 6 Comparative Example 3

[0067] The lithium ion batteries of Examples 6 to 10 and Comparative Examples 4 to 6 were subjected to relevant performance tests, and the test results are shown in Table 3.

[0068] Table 3

[0069]

[0070]

[0071] The lithium titanate negative electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 3 were tested for ion conductivity. The test results are shown in Table 4.

[0072] Table 4

[0073]

[0074] According to Table 3, compared with Comparative Examples 1 to 3, the lithium ion batteries prepared by Examples 1 to 5 have higher rate performance, that is, the introduction of lanthanum in the lattice and the combined effect of polyvinyl alcohol effectively improve the electrochemical performance of the lithium ion battery. The ionic conductivity test results in Table 4 prove that lanthanum oxide and polyvinyl alcohol improve the ionic conductivity of the lithium titanate negative electrode material.

[0075] By observation Figure 1(A) to Figure 1(D) From the microscopic morphology, it can be seen that the particle size of the lithium titanate negative electrode material prepared in Example 2 is about 3 um, and the particle size is relatively uniform. Compared with Comparative Example 1, the lithium titanate negative electrode material prepared in Example 2 presents a more complete spherical shape.

[0076] pass Figure 2 and Figure 3 XRD characterization shows that the introduction of lanthanum oxide can change the crystal structure and electronic structure of lithium titanate. Figure 2 In the experiment, the lithium titanate crystal form is relatively stable, and the characteristic peak of lanthanum is introduced (a peak No. 5 is obviously added at 37°), and no impurity peaks appear, which is consistent with the Figure 3 In contrast, the intensity of the characteristic peaks did not decrease after the introduction of polyvinyl alcohol and lanthanum oxide. Figure 3 There is no characteristic peak of lanthanum at 37°.

[0077] pass Figure 4 and Figure 5 The rate performance test shows that the cycle stability of lithium-ion batteries is improved after the introduction of polyvinyl alcohol and lanthanum oxide.

[0078] pass Figure 6It can be seen that the lithium-ion battery prepared by introducing polyvinyl alcohol and lanthanum oxide into the lithium titanate negative electrode material has good cycle stability, and various indicators tend to be stable during short-time charging and discharging.

[0079] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.

Claims

1. A method for preparing a lithium titanate negative electrode material, characterized in that: include: The titanium source, lithium source, lanthanum source, polyvinyl alcohol and solvent are mixed until uniform, and the mixture is spray-dried to obtain a precursor powder. The precursor powder is calcined at 700-900° C. for 5-10 hours, and cooled to room temperature to obtain a lithium titanate negative electrode material.

2. The preparation method according to claim 1, characterized in that: Calculated by molar fraction, the ratio of lithium in the lithium source to titanium in the titanium source is (4.1-4.7):(4.7-5.4), the ratio of the molar fraction of lithium in the lithium source, the molar fraction of lanthanum in the lanthanum source and the mass fraction of polyvinyl alcohol is (0.1-1):(0.001-0.05):(0.1-3), the unit of the mass fraction is g, and the unit of the molar fraction is mmol.

3. The preparation method according to claim 2, characterized in that: The solvent is one or a mixture of water, ethanol and isopropanol.

4. The preparation method according to claim 1, characterized in that: The inlet temperature of the spray drying is 180-210° C., the pressure of the spray drying is 0.1-0.5 MPa, and the feed rate of the spray drying is 100-500 mL / h.

5. The preparation method according to claim 1, characterized in that: In step 1, the ratio of the amount of lithium in the lithium source to the mass of the solvent is (200-300): (150-200), the unit of the amount of lithium is mmol, and the unit of the mass is g.

6. The lithium titanate negative electrode material obtained by the preparation method according to any one of claims 1 to 5.

7. A lithium titanate negative electrode plate, characterized in that: include: A current collector and a negative electrode material loaded on the current collector, wherein the negative electrode material is the lithium titanate negative electrode material as described in claim 6.

8. A method for preparing a lithium titanate negative electrode sheet, characterized in that: include: The lithium titanate negative electrode material, acetylene black, binder and N-methylpyrrolidone described in claim 6 are uniformly mixed to obtain an electrode slurry, and the electrode slurry is applied to the surface of the current collector and dried to obtain a lithium titanate negative electrode sheet, wherein the ratio of the lithium titanate negative electrode material, acetylene black and binder is (7-8.5):(0.5-2.0):(0.5-2.5) by mass.

9. Use of polyvinyl alcohol and lanthanum source in improving the ionic conductivity of lithium titanate.

10. Use of the lithium titanate negative electrode material according to claim 6 in a battery to improve the capacity retention rate.